THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE – SYSTEMATIC LITERATURE REVIEW - Jannah, Miftahul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Organizational culture is an important component that can influence employee performance. A positive organizational culture can encourage people to improve their performance. The goal of this study is to dig deeper into the impact of organizational culture on employee performance. Method: This study employs Systematic Literature Review (SLR). Results: A review of five journal publications revealed that organizational culture had an effect on employee performance in both government and private offices, with the exception of one article suggesting that organizational culture has no meaningful effect. Novelty: Using the SLR method, comparing several journals to investigate the impact of organizational culture on employee performance.